THE EFFECT OF RETAIL SERVICE, HEDONIC VALUE, AND OUTLET ATMOSPHERE ON THE IMPULSE PURCHASES OF IKEA ALAM SUTERA CUSTOMERS - Audrey Alya Shifa; Kevin Hilman Yusuf; Marbelle Ridaryanto; Nadya Estefania Brenaita (Universitas Pelita Harapan, 2022)
The purpose of this study is to analyze the factors that influence impulsive buying. The research used a quantitative descriptive approach with distribute online questionnaire to 50 respondents of the public in Jakarta to earn the data. The results showed that retail service influenced impulsive buying, hedonic value influenced impulsive buying, and store atmosphere had a significant positive effect on impulsive buying. The results of the test show that the value of sig < alpha (0.05) and ) means that retail services, hedonic values and store atmosphere simultaneously affect impulse buying.